Fellstones - Campbell, Ramsey, 1946- (Flame Tree Press, 2022)
Fellstones takes its name from seven objects on the village green. It's where Paul Dunstan was adopted by the Staveleys after his parents died in an accident for which he blames himself. The way the Staveleys tried to control him made him move away and change his name. Why were they obsessed with a strange song he seemed to have made up as a child? Now their daughter Adele has found him. By the time he discovers the cosmic truth about the stones, he may be trapped. There are other dark secrets he'll discover, and memories to confront. The Fellstones dream, but they're about to waken.--